2019
DOI: 10.3390/fib7040033
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Waste as a Reinforcement Particulate for Aluminum Metal Matrix Composite (AMMCs): A Review

Abstract: The desire to create sustainable development through research birthed this study. Over time, several authors have focused on the utilization of various chemical particulates as reinforcement constituents for metallic matric composites (MMCs) and aluminum metal matrix composites (AMMCs), which has thus far yielded positive outcomes for achieving the chemical, mechanical, microstructural, thermal, corrosion, and wear property improvement of various reinforced composites. However, this study focused on the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The use of agro-waste in the production of engineering materials is gaining wide acceptance due to its low cost, availability and the enormous advantage of reducing the rate of environmental pollution (Alaneme, Eze, & Bodunrin, 2015;Joseph & Babaremu, 2019). The use of ash sourced from agro waste such as rice husk, groundnut shell, bamboo leaf, coconut shell, sugarcane bagasse, corn cob, palm kernel and periwinkle shell have been identified as suitable ceramic reinforcement materials for synthesizing AMCs (Alaneme, Bodunrin, & Awe, 2018;Joseph & Babaremu, 2019;Kulkarni, Siddeswarappa, & Kumar, 2019). The authors reported that the ash forms of the mentioned agro wastes are rich in silicon and magnesium and could be deployed as reinforcement materials in AMCs.…”
Section: Agro-waste-based Ceramic Reinforcementsmentioning
confidence: 99%
“…The use of agro-waste in the production of engineering materials is gaining wide acceptance due to its low cost, availability and the enormous advantage of reducing the rate of environmental pollution (Alaneme, Eze, & Bodunrin, 2015;Joseph & Babaremu, 2019). The use of ash sourced from agro waste such as rice husk, groundnut shell, bamboo leaf, coconut shell, sugarcane bagasse, corn cob, palm kernel and periwinkle shell have been identified as suitable ceramic reinforcement materials for synthesizing AMCs (Alaneme, Bodunrin, & Awe, 2018;Joseph & Babaremu, 2019;Kulkarni, Siddeswarappa, & Kumar, 2019). The authors reported that the ash forms of the mentioned agro wastes are rich in silicon and magnesium and could be deployed as reinforcement materials in AMCs.…”
Section: Agro-waste-based Ceramic Reinforcementsmentioning
confidence: 99%
“…Graphite is one of the allotropes of crystalline carbon is known for its good electrical properties and high melting point which make it suitable for casting and moulding applications. This has led scientists to explore synthesizing graphite from several other sources to complement its natural source due to increased demand ( Raghavan et al., 2017 ; Joseph and Babaremu, 2019 ). Samsul et al.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium-based metal matrix composites and aluminium-silicon alloys have found usage in the production of a number of automotive engine machineries [6]. Based on these recent growths, there is a demand for composite materials possessing great chemical and mechanical characteristics including toughness, improved corrosion resistance and high hardness [7]. Recently, researches on metal matrix composites (MMC) suggest that these materials display advantageous industrial applications owing to their high resistance to elevated temperature and greater strength-toweight ratio.…”
Section: Introductionmentioning
confidence: 99%